ADOPSI INOVASI PROGRAM ANJUNGAN TERIMA MANDIRI (ATM) BERAS BADAN AMIL ZAKAT NASIONAL (BAZNAS) KABUPATEN SIAK - Muhammad Ilham; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The Rice Automatic Teller Machine (ATM) program from the National Board of Zakat (BAZNAS) of Siak Regency is one of the current technological developments. This program is a service technology innovation that was adopted to give an ease of services to the public quickly. The purpose of this research is to find out how the process of The Rice Automatic Teller Machine (ATM) program from the National Board of Zakat (BAZNAS) of Siak Regency runs and what supporting factors are in the adoption of this innovation. This research uses a purposive sampling technique. The type of the research is qualitative research. It uses a descriptive approach. The data collection techniques are observation, interviews, documentation and for subsequent analysis. The results of this research show that: first, the adoption of this innovation program has been running optimally. Second, the supporting factors of the adoption of this innovation are machine technology, good leadership, socialization, and public trust. Keywords: Adoption of Innovation, Program, service